Goodbye Washington Consensus, Hello Washington Confusion? A Review of the World Bank's Economic Growth in the 1990s: Learning from a Decade of Reform - Rodrik, Dani (Journal of Economic Literature, 2006)
Proponents and critics alike agree that the policies spawned by the Washington Consensus have not produced the desired results. The debate now is not over whether the Washington Consensus is dead or alive, but over what will replace it. An important marker in this intellectual terrain is the World Bank's Economic Growth in the 1990s: Learning from a Decade of Reform (2005). With its emphasis on humility, policy diversity, selective and modest reforms, and experimentation, this is a rather extraordinary document demonstrating the extent to which the thinking of the development policy community has been transformed over the years. But there are other competing perspectives as well. One (trumpeted elsewhere in Washington) puts faith on extensive institutional reform, and another (exemplified by the U.N. Millennium Report) puts faith on foreign aid. Sorting intelligently among these diverse perspectives requires an explicitly diagnostic approach that recognizes that the binding constraints on growth differ from setting to setting.